OPTIMALISASI PENGGUNAAN ABSHAR DALAM BELAJAR DAN PEMBELAJARAN - Hilmi Hilmi (UIN AR-RANIRY, 2015)
Using Abshar (visual) as one of the resources in learning has increased from one period to the next period. The more optimal in using abshar, the more successful in learning activities will be. The discovery of various theories in various branches of science shows the result of reading kauniyah from scholars. Furthermore, nowadays is the time of the sophisticated and modern where abshar has greater role in learning. People who do not use abshar optimally will fall behind and backwardness, because various means of science and technology can only be used by optimizing the use of abshar. Basically, long time ago the Al- Qur'an as a guide for all human beings has talked about optimizing the use of this abshar both in learning and teaching activities. This paper by using the approach of the Thematic Study (Maudhu'i) will try to review the use of optimization abshar in learning activities and teaching learning process from the perspective of the Al-Qur’an.